Intelligent dashboard with speech enhancement - Abdul Rahman, Abdul Wahab; Tan, Eng Chong; Abut, Huseyin (1997)
The increasing demand for mobile multimedia communication prompted extensive studies on implementing effective and optimum way to communicate in the vehicular environment. The proposed system cover the analysis and cancellation/suppression of the various noise in a vehicular environment ranging from engine noise, wind noise to road noise. In addition it is critical to also understand the echoes that can be generated due to the effect of a vehicle chamber. All these noises and unwanted signals impede on the speech performance and have been a cause of clarity in speeches even on an uncompressed voice. The compressed speech uses the LPC algorithm in the VOCODER and these worsen the speech clarity and could be disastrous, where speech could be totally unrecognisable. Hence, the intelligent dashboard would require microphone arrays and a multitasking system to handle the vast processing requirement. Numerous asynchronous scheduling tasks necessitate the architecture to be re-configurable. A cost-effective technology for this would be to employ a powerful digital signal processing (DSP) sub-system equipped with the necessary support electronics.